Mobile health technology to improve emergent frailty after lung transplantation. Issue 4 (5th February 2021) - Diamond, Joshua M.; Courtwright, Andrew M.; Balar, Priya; Oyster, Michelle; Zaleski, Derek; Adler, Joe; Brown, Melanie; Hays, Steven R.; Sutter, Nicole; Garvey, Chris; Kukreja, Jasleen; Gao, Ying; et al.
Abstract: We evaluated the feasibility, safety, and efficacy of a mHealth‐supported physical rehabilitation intervention to treat frailty in a pilot study of 18 lung transplant recipients. Frail recipients were defined by a short physical performance battery (SPPB score ≤7). The primary intervention modality was Aidcube, a customizable rehabilitation mHealth platform. Our primary aims included tolerability, feasibility, and acceptability of use of the platform, and secondary outcomes were changes in SPPB and in scores of physical activity, and disability measured using the Duke Activity Status Index (DASI) and Lung Transplant‐Value Life Activities (LT‐VLA). Notably, no adverse events were reported. Subjects reported the app was easy to use, usability improved over time, and the app enhanced motivation to engage in rehabilitation. Comments highlighted the complexities of immediate post‐transplant rehabilitation, including functional decline, pain, tremor, and fatigue. At the end of the intervention, SPPB scores improved a median of 5 points from a baseline of 4. Physical activity and patient‐reported disability also improved. The DASI improved from 4.5 to 19.8 and LT‐VLA score improved from 2 to 0.59 at closeout. Overall, utilization of a mHealth rehabilitation platform was safe and well received. Remote rehabilitation was associated with improvements in frailty, physical activity and disability. Future studies should evaluate mHealth treatment modalities in larger‐scale randomized trials of lung transplant recipients.